Age‐related change in task‐evoked amygdala—prefrontal circuitry: A multiverse approach with an accelerated longitudinal cohort aged 4–22 years. Issue 10 (8th April 2022) - Bloom, Paul Alexander; VanTieghem, Michelle; Gabard‐Durnam, Laurel; Gee, Dylan G.; Flannery, Jessica; Caldera, Christina; Goff, Bonnie; Telzer, Eva H.; Humphreys, Kathryn L.; Fareri, Dominic S.; Shapiro, Mor; Algharazi, Sameah; et al.
Abstract: The amygdala and its connections with medial prefrontal cortex (mPFC) play central roles in the development of emotional processes. While several studies have suggested that this circuitry exhibits functional changes across the first two decades of life, findings have been mixed ‐ perhaps resulting from differences in analytic choices across studies. Here we used multiverse analyses to examine the robustness of task‐based amygdala—mPFC function findings to analytic choices within the context of an accelerated longitudinal design (4–22 years‐old; N  = 98; 183 scans; 1–3 scans/participant). Participants recruited from the greater Los Angeles area completed an event‐related emotional face (fear, neutral) task. Parallel analyses varying in preprocessing and modeling choices found that age‐related change estimates for amygdala reactivity were more robust than task‐evoked amygdala—mPFC functional connectivity to varied analytical choices. Specification curves indicated evidence for age‐related decreases in amygdala reactivity to faces, though within‐participant changes in amygdala reactivity could not be differentiated from between‐participant differences. In contrast, amygdala—mPFC functional connectivity results varied across methods much more, and evidence for age‐related change in amygdala—mPFC connectivity was not consistent. Generalized psychophysiological interaction (gPPI) measurements of connectivity were especially sensitive to whether a deconvolution step was applied. Our findings demonstrate the importance of assessing the robustness of findings to analysis choices, although the age‐related changes in our current work cannot be overinterpreted given low test–retest reliability. Together, these findings highlight both the challenges in estimating developmental change in longitudinal cohorts and the value of multiverse approaches in developmental neuroimaging for assessing robustness of results. Abstract : The current study used multiverse analyses to examine age‐related changes in task‐evoked amygdala–mPFC circuitry in an accelerated longitudinal cohort ages 4–22 years. We found evidence that in the context of this task, age‐related change estimates for amygdala reactivity to faces were more robust to analytic decisions than were estimates of age‐related change in amygdala—mPFC functional connectivity.